Acute vision loss in neurosurgical and neurological disorders (Ukrainian Journal of Ophthalmology, 2026)
The evaluation and management of acute vision loss is a multidisciplinary problem. Aneurysmal rupture producing a subarachnoid hemorrhage, craniocerebral injury, internal carotid artery disease, migraines (including ophthalmic and retinal ones), and lesions in the chiasmal and sellar regions, intracranial hypertension and demyelinating disorders are common neurosurgical and neurological causes of this condition. Neuro-ophthalmological manifestations include retinal hemorrhage and vascular occlusion, ischemic, traumatic and compressive neuropathy, neuritis and papilledema. Early detection and adequate assessment of neuro-ophthalmological symptoms are of primary importance.
Keywords: vision; acute loss; neurosurgical causes; neuro-ophthalmological manifestations; detection